India Beyond India: Dilemmas of Belonging - Hermann, Elfriede; Fuhse, Antonie (Universitätsverlag Göttingen, 2018)
People's transnational mobilities, their activities to build homes in their countries of residence and their connectivities have resulted in multiplicities of belonging to encountered, imagined and represented communities operating within various political contexts. Migrants and their descendants labor to form and transform relations with their country of origin and of residence. People who see their origins in India but are now living elsewhere are a case in point. They have been establishing worldwide home places, whose growing number and vibrancy invite reconsideration of Indian diasporic communities and contexts in terms of 'India(s) beyond India.' Issues of belonging in Indian diasporas include questions of membership not only in the nation of previous and present residence and/or the nation of origin, but also in other communities and networks in political, economic, religious and social realms at local, regional or global levels. Yet, belonging - and especially simultaneous belonging - to various formations is rarely unambiguous. Rather, belonging in all its modes may entail dilemmas that arise from inclusions and exclusions. Bearing in mind such processes, the contributions to this volume endeavor to provide answers to the question of what kinds of difficulties members of Indian communities abroad encounter in connection with their identifications with and participation in specific collectivities. The underlying argument of all the essays collected is that members of Indian diasporas develop strategies to cope with the dilemmas they face in connection with their sense of belonging to particular communities, while they are subjected to specific power relationships. Thus, the volume sheds light on the ways in which dilemmas of belonging are being negotiated in intercultural fields.